Odpowiedź:
A)
4x - 3(x - 3) = x - 4
4x - 3x + 9 = x - 4
x - x = -4 - 9
0 = -13
rownanie sprzeczne
nie ma rozwiazan
b)
2x - (3 - 2x) = 5 + x - x
2x - 3 + 2x = 5
4x = 5 + 3 /:4
x = 8/4 = 2
c)
5(x - 2) + (3 + x) = 6x - 7
5x - 10 + 3 + x = 6x - 7
6x - 6x = -7 + 7
0 = 0
rownanie tozsamosciowe
nieskonczenie wiele rozwiazan wsor liczb rzeczywistych
d)
-(x + 1) + 8x = 5x - 9
-x - 1 + 8x = 5x - 9
7x - 5x = -9 + 1
2x = -8 /:2
x = -4
e)
2(2x + 1) = 4x + 3
4x + 2 = 4x + 3
4x - 4x = 3 - 2
0 = 1
rownanie sprzeczne
f)
9x + 3 = 7(x - 2) + 17
9x + 3 = 7x - 14 + 17
9x - 7x = 3 - 3
2x = 0 /:2
x = 0
g)
5x - 9 + x = 3(2x - 3)
6x - 9 = 6x - 9
6x - 6x = -9 + 9
rownanie tozsamosciowe
h)
4(3x - 2) + 5 = 2(6x - 4) + x
12x - 8 + 5 = 12x - 8 + x
12x - 3 = 13x - 8
12x - 13x = -8 + 3
-x = -5 /*(-1)
x = 5
Szczegółowe wyjaśnienie: